Sub-majer's challenge - Modesitt, L. E., Jr., 1943- (Modesitt, L. E., Jr., 1943- Saga of Recluce., 2025)
"L. E. Modesitt, Jr. continues his Saga of Recluce series with Sub-Majer's Challenge. The epic scope of the world, the intricate magic system, and a reluctant hero, continue the story arc that began with From the Forest and continued with Overcaptain. Alyiakal, a sub-majer in the Mirror Lancers of Cyador, The Empire of Light, is serving the last year of his tour as commanding officer of a remote border post. Rumors hint that the Cerlynese Duke, in retaliation for Alyiakal's success in a border skirmish, is readying an even larger attack. Against terrible odds, Alyiakal gains victory and a promotion. He takes leave only to discover his courtship of Saelora is opposed by her mother. Disappointed and reposted to the remote Pemedra Post-again-Alyiakal must navigate a rapidly developing war. In the midst of this, when forces outnumbering his command five to one attack a small town, Alyiakal is given orders to drive out the invaders, whatever the cost"--